2021
DOI: 10.25299/kiat.2021.vol32(2).8273
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepuasan dalam Memoderasi Citra Perusahaan dan Kepercayaan Terhadap Loyalitas Pengguna Aplikasi Go-Jek di Kota Pekanbaru

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh kepuasan dalam memoderasi citra perusahaan dan kepercayaan terhadap loyalitas pengguna aplikasi Go-Jek di Kota Pekanbaru. Penelitian ini menggunakan data primer yaitu data yang diperoleh dari hasil kuesioner kepada pengguna Go-Jek di Kota Pekanbaru. Data sekunder yang diperoleh berkaitan dengan literatur yang berhubungan dengan peneliti. Sampel dalam penelitian ini sebanyak 160 orang, diambil dengan metode Accidental Sampling. Metode analisis yang digunakan da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Therefore, if Mojokerto City Center for Featured Products successfully achieves a high level of user happiness, it will subsequently enhance customer loyalty, resulting in frequent purchases at the Mojokerto City Center for Featured Products. The findings of Nurutami, Sri Sitiani, Marnis, Kornita, and Sri Endang (2021) align with previous research, indicating that customer pleasure has a significant impact on customer loyalty.…”
Section: The Influence Of Customer Satisfaction On Customer Loyalty A...supporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, if Mojokerto City Center for Featured Products successfully achieves a high level of user happiness, it will subsequently enhance customer loyalty, resulting in frequent purchases at the Mojokerto City Center for Featured Products. The findings of Nurutami, Sri Sitiani, Marnis, Kornita, and Sri Endang (2021) align with previous research, indicating that customer pleasure has a significant impact on customer loyalty.…”
Section: The Influence Of Customer Satisfaction On Customer Loyalty A...supporting
confidence: 87%
“…In other words, the moderating effect of company image on loyalty demonstrates a substantial positive association with loyalty. According to a study conducted by Nurutami, Sri Sitiani, Marnis, Kornita, and Sri Endang (2021), it has been shown that satisfaction plays a moderating role in the relationship between business image and loyalty.…”
Section: The Moderating Effect Of Customer Satisfaction With Store Im...mentioning
confidence: 99%